Determinación de las necesidades hídricas del cultivo de tomate de mesa (Solanum Lycopercum, V. Sheila), mediante el lisimetro volumetrico, en el sector El Porvenir perteneciente al sistema de riego Campana-Malacatos. - Valverde Poma, Andrea del Cisne (2017)
The present investigation was made in the Rumishitana district in the sector El Porvenir to the South east of the City of Loja, whose location is 10 Km from the parochial head and 20 Km from the city of Loja, to an altitude of 1665 mamsl. Being the primary target of this investigation to contribute to the determination of technical parameters on the hydric necessities of the tomato crop (Solanum Lycoperscum, V. Sheila) in order to improve the efficiency of the use of the water, for which it is proposed to 1). To calculate the evapotranspiration of the reference crop (ETo) through the application of the Penman-Monteith method. 2). To calculate the evapotranspiration of the tomato crop (ETc) in its different phenological phases, using the direct method of the volumetric lysimeter. 3). To determine the crop coefficient (Kc) considering the ETo calculated with the Penman-Monteith method, and the ETc determined with the volumetric lysimeter method for the phenological phases of the tomato crop. The Phenological phases considered were: Initial phase (15 days), development phase (56 days), middle phase (48 days) and the final phase (28 days), for a total cycle of 145 days after transplantation. The sowing area was 25.00 m2 where two lysimeters of 1m2 each were located. The cultivation that was implanted was the table tomato, hybrid Sheila variety with a planting distance of 0.40 m between rows and 0.50 m between plants. The reference evapotranspiration (ETo) was estimated by the Penman-Monteith (FAO) method using Cropwat 8.0 software, obtaining a higher value showed in the final phase 4.05 mm/day; while the lowest value is shown in the initial phase with 3.58 m/day. On the other hand, the crop evapotranspiration (ETc) which was estimated through the volumetric lysimeter, determining that the highest ETc value, is presented in the middle phase with 4.44 mm/day, while the lowest value is present in the initial phase with 1.04 mm/day. In this way, the Kc is given by the relation: Kc = ETc/ETo in each of the phenological phases. The values resulting from Kc presented an increasing behavior until the middle phase or fruit growth, and a decrease during the final or maturation phase; the values for the phenological phases were: Initial or post-transplant phase (0.29), phase of development or rapid growth (0.94), middle phase or fruit growth (1.20) and final phase or maturation (1.05). Finally, it was determined that the total water requirement for the vegetative period of the crop is 1395.6 mm, equivalent to 13956 m3/ha, achieving a productivity of 51 ton/ha. Keywords: lysimeter, evapotranspiration, crop coefficient (Kc).